2020
DOI: 10.3389/fendo.2020.579420
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Estrogen Receptor in Immune Cells and Its Role in Immune-Related Diseases

Abstract: G protein-coupled estrogen receptor 1 (GPER1), is a functional estrogen receptor involved in estrogen related actions on several systems including processes of the nervous, reproductive, metabolic, cardiovascular, and immune system. Regarding the latter, GPER is expressed in peripheral B and T lymphocytes as well as in monocytes, eosinophils, and neutrophils. Several studies have implicated GPER in immune-mediated diseases like multiple sclerosis, Parkinson’s disease, and atherosclerosis-related inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 98 publications
(131 reference statements)
0
44
0
1
Order By: Relevance
“…For example, tumor-associated macrophages contribute to tumor progression and metastasis by secreting multiple growth factors and inflammatory cytokines into the tumor microenvironment [ 112 , 113 ]. Estrogens display multiple effects on the immune system, including both development and function [ 114 , 115 , 116 ]. ERα, ERβ, and GPER knockout (KO) mouse studies revealed that ERα mediates an early developmental blockage of thymocytes, whereas GPER is required for apoptosis of T cell double-positive thymocytes [ 117 ].…”
Section: Gper In the Immune Systemmentioning
confidence: 99%
“…For example, tumor-associated macrophages contribute to tumor progression and metastasis by secreting multiple growth factors and inflammatory cytokines into the tumor microenvironment [ 112 , 113 ]. Estrogens display multiple effects on the immune system, including both development and function [ 114 , 115 , 116 ]. ERα, ERβ, and GPER knockout (KO) mouse studies revealed that ERα mediates an early developmental blockage of thymocytes, whereas GPER is required for apoptosis of T cell double-positive thymocytes [ 117 ].…”
Section: Gper In the Immune Systemmentioning
confidence: 99%
“…It was shown that G-1 suppressed proliferation in several types of cancer cell lines by inhibiting NF-κB phosphorylation and cross-talk between GPER signaling and NF-κB signaling has been noted. For example, GPER activation reduces the secretion of inflammatory factors, such as IL-6 and TNF-α from monocyte/macrophages in mice, suggesting that GPER indirectly regulates NF-κB and reduces inflammation ( 42 , 43 ). In human, GPER activation alleviates inflammation by interacting directly with the ER-α splice variant and the p65 subunit of NF-κB in primary monocytes ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that GPER plays diverse functions depending on cell types, underlying pathology, and tumor micro-environment. GPER is expressed in the early stages of immune cells including B cells ( 43 ). But related functional studies are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the immune system, GPER is expressed in each population of immune cells, including peripheral B and T lymphocytes, monocytes, eosinophils, and neutrophils. 65 In addition, it regulates estrogenic effects on immune functions in humans and other species. 66 , 67 The immunomodulatory effect of GPER has also been beneficial in immune-mediated diseases such as multiple sclerosis, liver fibrosis, and autoimmune encephalomyelitis by reducing the levels of inflammatory cytokines and upregulating programmed death-1 (PD-1) on CD4 + Foxp3 + regulatory T cells.…”
Section: Gper In Metabolic Syndrome Clinical Targeted-therapy and Tmentioning
confidence: 99%